PERAN LINGKUNGAN TERHADAP PARTISIPASI DALAM KEGIATAN OLAHRAGA SISWA/SISWI MTs NURUL HAQ, KARANG BEJELO, KELURAHAN GONJAK, KECAMATAN PRAYA - Herlina Herlina; Zakir Burhan; Lalu Hasan Ashari; Afritoma Abdullah; Agus Sari M Ripai (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2024)
This research was qualitative method . The samples used in this research were MTs Nurul Haq students, physical education teachers and parents of students. The technique used in sampling is purposive sampling. Data collection techniques using observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. From the interviews that were conducted, the results showed that the physical, social and psychological environment plays an important role in the sports activities of MTs Nurul Haq students, because it increases motivation and creates enthusiasm for students in sports at school. The conclusion in this research is that the physical, social and psychological environment plays an important role in the sports activities of MTs Nurul Haq students. Recommended 1). For schools, existing infrastructure should be increased so that students' interest in sports increases. 2). For teachers when providing sports lessons to students, it would be better to provide motivation after each exercise so that their enthusiasm becomes greater.